2014
DOI: 10.1049/el.2014.0993
|View full text |Cite
|
Sign up to set email alerts
|

Approaching real‐time terahertz imaging with photo‐induced coded apertures and compressed sensing

Abstract: Photo-induced coded-aperture imaging (PI-CAI) based on compressed sensing (CS) at 590 GHz using a WR-1.5 (500-750 GHz) vector network analyser is demonstrated. For a 256-pixel (16 × 16) frame, the acquisition time can be reduced by 40%, as compared with PI-CAI without CS, while maintaining high imaging quality. On the basis of this approach, it is envisioned that real-time (26 fps) THz imaging with 1000 pixels (32 × 32) can be realised using high-speed digital micromirror device chipsets and optimised data-acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Several modulation methods based on the opticallyinduced physical processes in semiconductors are proposed so far 7,[13][14][15][16][17][18] . In particular, pure Si and GaAs crystals have been used for this purpose 15 .…”
mentioning
confidence: 99%
“…Several modulation methods based on the opticallyinduced physical processes in semiconductors are proposed so far 7,[13][14][15][16][17][18] . In particular, pure Si and GaAs crystals have been used for this purpose 15 .…”
mentioning
confidence: 99%
“…In 2008, Chan et al [7] adopted standard printed circuit boards as the random matrix to modulate the terahertz transmission, and demonstrated a THz single-pixel imaging by further combining the compressed sensing (CS) algorithm. In order to avoid the use of moving masks, which are difficult to align, Watts et al [8] made use of a metamaterial spatial modulator, Sensale-Rodriguez et al [9] employed arrays of graphene electro-absorption modulators, and Kannegulla et al [10] and Shams et al [11] demonstrated photo-induced coded-aperture imaging using a semiconductor illuminated by a commercial available digital light processing projector. Recently, silicon wafers have been widely used as THz photomodulators, based on which Stantchev et al [12,13] demonstrated THz superresolution imaging.…”
Section: Introductionmentioning
confidence: 99%
“…When the laser spot reflected by the DMD is changed from black to white, the THz transmittance through the passivated silicon decreases from a high level to a low level, i.e., from "1" to "0". For terahertz single-pixel imaging based on compressed sensing (CS) approach [7,11,21], the target, such as a cartwheel patterned in a gold film, is deposited on top of the front SiO 2 layer. For a THz image of N × N pixels to be measured, a series of masks are projected onto the target.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, those systems are still quite large to get a sufficient resolution. Lately, pixels working around 300 GHz [11,12] have been developed and seem promising to reduce SWAP-C. One can overcome the technological difficulty of getting a high-resolution array of subTHz sensors by using a single-pixel camera with a coded aperture instead [13]. A full passive imaging system has been tested [14] with a dual-polarization W-band (75 to 110 GHz) radiometer.…”
Section: Introductionmentioning
confidence: 99%